Reclaiming information and communication technologies for development /Tim Unwin. - Unwin, Tim.
This book draws on the author's 15 years of practical and conceptual experience of research and practice in delivering development initiatives that effectively use information and communication technologies (ICTs) to empower some of the world's poorest and most marginalized people.